Testosterone in COVID-19: An Adversary Bane or Comrade Boon - Al-kuraishy, Hayder M.; Al-Gareeb, Ali I.; Faidah, Hani; Alexiou, Athanasios; Batiha, Gaber El-Saber (Frontiers in Cellular and Infection Microbiology, 2021)
Covid-19 is a pandemic disease caused by severe acute respiratory coronavirus 2 (SARS-CoV-2), leads to pulmonary manifestations like acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). In addition, Covid-19 may cause extra-pulmonary manifestation like a testicular injury. Both high and low levels of testosterone could affect the severity of Covid-19. Herein, there is substantial controversy regarding testosterone's potential role in SARS-CoV-2 infection and Covid-19 severity. Therefore, the present study aimed to review and elucidate the assorted view of preponderance regarding testosterone's beneficial and harmful effects in Covid-19. A related literature search in PubMed, Scopus, Web of Science, Google Scholar, and Science Direct was done. All published articles related to the role of testosterone and Covid-19 were included in this mini-review. Testosterone's beneficial effects in Covid-19 are through inhibition of pro-inflammatory cytokines, augmentation of anti-inflammatory cytokines, modulation of the immune response, attenuation of oxidative stress and endothelial dysfunction. However, testosterone's harmful effects in Covid-19 are due to augmentation of transmembrane protease serine 2 (TMPRSS2), which is essential for cleaving and activating SARS-CoV-2 spike protein during acute SARS-CoV-2 infection. Most published studies illustrated that low testosterone levels are linked with Covid-19 severity. A low testosterone level in Covid-19 is mainly due to testicular injury, the primary source of testosterone.